EKSISTENSI BAHASA JAWA DALAM BIDANG PERSAWAHAN DI DESA POMBULAA JAYA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - La Sudu (Seshiski: Southeast Journal of Language and Literary Studies, 2026)
This research was conducted in Pombulaa Jaya Village, Konda District, South Konawe Regency. The majority of the population in Pombulaa Jaya Village are Javanese transmigrants and have livelihoods in the field of rice farming. The presence of these Javanese transmigrants adds to the uniqueness of local languages in Southeast Sulawesi. Language survival is related to whether the language still endures or not. If it still persists, whether it is still used daily as a means of communication among the community. Language empowerment can be carried out directly through two processes, namely the process of language maintenance and the process of language shift. Research on "The Survival of the Javanese Language in the Field of Rice Farming in Pombulaa Jaya Village, Konda District, South Konawe Regency (An Ecolinguistic Study)" is important to conduct because currently there is a shift in the use of the Javanese language in Pombulaa Jaya Village. Today's younger generation prefers Indonesian in their daily communication. They no longer know the meanings of Javanese lexicons in the field of farming. This research is expected to be able to raise awareness among the local community about the importance of preserving regional languages, especially Javanese, in the field of farming.